2009
DOI: 10.1103/physrevb.79.165202
|View full text |Cite
|
Sign up to set email alerts
|

Electronic structure, donor and acceptor transitions, and magnetism of3dimpurities inIn2O3and ZnO

Abstract: 3d transition impurities in wide-gap oxides may function as donor/acceptor defects to modify carrier concentrations, and as magnetic elements to induce collective magnetism. Previous first-principles calculations have been crippled by the LDA error, where the occupation of the 3d-induced levels is incorrect due to spurious charge spilling into the misrepresented host conduction band, and have only considered magnetism and carrier doping separately. We employ a band-structure-corrected theory, and present simul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
67
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 115 publications
(79 citation statements)
references
References 44 publications
12
67
0
Order By: Relevance
“…We have also shown that trends on transition energies, for any of the three sites, could only be rationalized if they were discussed in terms of the increasing occupation of 3d-related states in the bandgap. Such trends are consistent with what would be expected for transition metal impurities in other semiconductors in either isolated configurations 29,30 or forming complexes with other defects 25,31 . Fig.…”
Section: Discussionsupporting
confidence: 78%
“…We have also shown that trends on transition energies, for any of the three sites, could only be rationalized if they were discussed in terms of the increasing occupation of 3d-related states in the bandgap. Such trends are consistent with what would be expected for transition metal impurities in other semiconductors in either isolated configurations 29,30 or forming complexes with other defects 25,31 . Fig.…”
Section: Discussionsupporting
confidence: 78%
“…However, certain impurity-host combinations might have a legitimate impurity level in resonance with the host conduction band; if that level is not too high inside the conduction band, it might be partially occupied by additional intentional donor doping, creating the desired partial occupancy and hence ferromagnetism. This idea led to a search for 3d impurities in ZnO and In 2 O 3 [38,41,[43][44][45][46] that have levels in resonance with the lowest part of the host conduction band. It is important here to note that the relevant quantity describing the energy of the TM-impurity "level" is the quasiparticle energy, that is, the electron addition energy into the unoccupied defect state.…”
Section: Problem 1: False Occupancymentioning
confidence: 99%
“…It is therefore possible that the ferromagnetic contribution, which increases upon decreasing the Ag concentration, originates from the presence of defects inside the ZnO matrix. It seems therefore that the ferromagnetic contribution is related to structural defects such as Zn interstitials or O vacancies as previously reported [11][12][13][39][40][41]. These defects, which were claimed to induce ferromagnetic properties even in pure and usually nonmagnetic oxides such as ZnO, TiO 2 , etc., are also present in ZnO:Co thin films giving rise to a ferromagnetic signal of the same order of magnitude as in the samples with additional Ag-doping.…”
Section: Resultsmentioning
confidence: 84%
“…By extension, it was further assumed that Co doped ZnO could exhibit similar interesting properties. However, the opinions on the ZnO:Co as a diluted magnetic semiconductor (DMS) are still divided in the scientific community between the groups that are convinced of the intrinsic nature of ferromagnetism [2][3][4] and those who attribute the ferromagnetic properties to the presence of parasitic phases and/or structural defects [5][6][7][8][9][10][11][12][13]. It is, on the other hand, reported that no ferromagnetic behavior was observed in numerous thin films or bulk samples regardless of the different synthesis routes (molecular beam epitaxy [9], hydrothermal technique [14,15], co-precipitation [16][17][18][19], sol-gel [20,21], or mechanosynthesis [22]).…”
Section: Introductionmentioning
confidence: 99%